Development and validation of the technology-facilitated sexual violence myth acceptance scale - Gray, Kate V.; Aranda, María; Domínguez-Lara, Sergio; Sánchez-Villena, Andy Rick (Anales de Psicología / Annals of Psychology, 2026)
Technology-facilitated sexual violence (TFSV) is an emerging form of gender-based violence that encompasses behaviours such as image-based abuse, online harassment, and coercion. While research on the prevalence and impact of TFSV has grown, there is a lack of validated measures assessing attitudes toward these behaviours. This study aimed to develop and validate the Technology-Facilitated Sexual Violence Myth Acceptance (TFSVMA) scale. A systematic review of the literature informed item generation, followed by expert panel evaluations and a pilot study to establish content validity. A total of 433 participants completed the initial 47-item scale, which underwent exploratory and confirmatory factor and network analyses. A bifactor model yielded the best fit; however indices supported essential unidimensionality, resulting in a final 12-item scale measuring TFSV myth acceptance (TFSVMA). The TFSVMA demonstrated strong internal consistency (α = .83), construct validity, and measurement invariance across demographic groups. Convergent validity was supported through correlations with existing measures of sexual violence myth acceptance. This scale provides a psychometrically sound tool for assessing attitudes toward TFSV, with implications for research, prevention, and intervention strategies.